A Web-Based Intelligent System for Awareness and Early Identification of Retinal Diseases - S. Sajithabanu; C. Indra Devi; R. Sowmiya; Asifa Farhana M; Naveetha Thaslim M (Journal of Computer Based Parallel Programming, 2026)
Vision problems related to retinal diseases have emerged as a serious global health concern. Diseases like diabetic retinopathy, glaucoma, and cataracts often develop gradually and may not be recognized until later stages. Awareness and access to reliable medical information are crucial for preventing vision loss. However, people are often unaware of information related to retinal diseases, including symptoms and prevention methods. The purpose of the research is to introduce a web-based, intelligent system for promoting awareness and facilitating early detection of retinal diseases. The system provides reliable and organized information related to common eye diseases, including symptoms, causes, risk factors, prevention, and treatment. This web application is developed using modern web technologies, including HTML, CSS, and JavaScript. The research attempts to bridge the gap between medical knowledge and awareness by providing reliable information related to eye health in an easily understandable format. People can learn about different eye diseases and understand the importance of early diagnosis and eye checkups. This web application also demonstrates the potential use of digital technologies in promoting healthcare awareness. This web application is also useful for promoting preventive healthcare.